2019
DOI: 10.1016/j.cell.2018.11.024
|View full text |Cite
|
Sign up to set email alerts
|

UBQLN4 Represses Homologous Recombination and Is Overexpressed in Aggressive Tumors

Abstract: Graphical Abstract Highlights d Homozygous UBQLN4 germline mutations lead to a genome instability syndrome d UBQLN4 removes ubiquitylated MRE11 from damaged chromatin to curtail DSB resection d UBQLN4 overexpression represses HRR and promotes the use of NHEJ for DSB repair d UBQLN4 overexpression in tumors promotes PARP1 inhibitor sensitivity SUMMARY Genomic instability can be a hallmark of both human genetic disease and cancer. We identify a deleterious UBQLN4 mutation in families with an autosomal recessive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
147
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(157 citation statements)
references
References 30 publications
3
147
1
1
Order By: Relevance
“…6 In affected patients, as well as in C. elegans ubql-1 mutants, the nematode ortholog of UBQLN4, we observed an increase of HR usage, fully in line with a functional defect of UBQLN4-mediated MRE11 turnover. 6 In healthy individuals, overt accumulation of ubiquitylated MRE11 on damaged chromatin is prevented by UBQLN4. Intriguingly, the interaction of MRE11 and UBQLN4 is regulated by ATM.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…6 In affected patients, as well as in C. elegans ubql-1 mutants, the nematode ortholog of UBQLN4, we observed an increase of HR usage, fully in line with a functional defect of UBQLN4-mediated MRE11 turnover. 6 In healthy individuals, overt accumulation of ubiquitylated MRE11 on damaged chromatin is prevented by UBQLN4. Intriguingly, the interaction of MRE11 and UBQLN4 is regulated by ATM.…”
supporting
confidence: 65%
“…6 We found that the proteasomal shuttle factor UBQLN4 binds to ubiquitylated MRE11 via its Ubiquitin-associated (UBA) domain and promotes its degradation, thus limiting the initiation of DNA end resection. 6 In affected patients, as well as in C. elegans ubql-1 mutants, the nematode ortholog of UBQLN4, we observed an increase of HR usage, fully in line with a functional defect of UBQLN4-mediated MRE11 turnover. 6 In healthy individuals, overt accumulation of ubiquitylated MRE11 on damaged chromatin is prevented by UBQLN4.…”
mentioning
confidence: 95%
“…This process is achieved through a defined order of events: phosphorylation of H2AX and MDC1, followed by recruitment of the RNF8 and RNF168 ubiquitin ligases, followed by ubiquitylation of H2A and recruitment of 53BP1, whose phosphorylation by ATM serves as a docking platform for RIF1 and, indirectly, the REV7–SHIELDIN complex (Fig ). In addition, ATM limits resection by phosphorylating the proteasomal shuttle factor UBQLN4, which leads to degradation of MRE11, a component of the MRN complex required for initial steps in resection (Jachimowicz et al , ). Paradoxically, ATM may also promote resection by phosphorylating CtIP, a key factor required for resection initiation (Shibata et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquilin -2 is involved in migration and invasion of breast cancer [10] and lung cancer cells [11]. A recent study showed that UBQLN4 could curtail HRR activity by removing MRE11 from damaged chromatin and provide a therapeutic target for PARP1 inhibitor treatment in UBQLN4-overexpressing tumors [12]. Ubiquilin -4 acts as a tumor suppressor during the progression of gastric cancer by inducing cell cycle arrest and senescence via the extracellular signal-regulated kinases (ERK) signaling pathway [13,14].…”
mentioning
confidence: 99%